2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.177-133
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Heart Sound Signals Based on AR Model

Abstract: Heart sounds reflect information of the mechanical contraction of the heart in both of the Specificity (Sp) and overall score are respectively 0.87, 0.61, and 0.74.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The purpose of using the HSMM model in this study was the estimation of the probability density function of the expected remaining time in each state. He and Zhang (2016) segmented PCG data based on wavelet decomposition and normalized Shannon energy. Pratima and Emin extracted feature vectors by dividing each cardiac cycle into 35 frames where each frame had a length of 150 ms and slide size of 25 ms (Upretee and Mehmet Emin 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of using the HSMM model in this study was the estimation of the probability density function of the expected remaining time in each state. He and Zhang (2016) segmented PCG data based on wavelet decomposition and normalized Shannon energy. Pratima and Emin extracted feature vectors by dividing each cardiac cycle into 35 frames where each frame had a length of 150 ms and slide size of 25 ms (Upretee and Mehmet Emin 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the fact that the SVM (Bouril and Aleinikava 2016) and LSTM (Christopher Schölzel et al 2016) have shown good classification accuracies of 78.64% and 74.9%, respectively, researchers have carried out relevant studies by utilizing different features and classification techniques to achieve better accuracy (Homsi and Medina 2016, Grzegorczyk et al 2016, Ibarra-Hernández and Bertin 2018. Runnan classified the PCG signal by using an autoregressive (AR) model with an accuracy of 74% (He and Zhang 2016). In Mandal et al (2014) ICA was utilized and ten independent components were extracted.…”
Section: Introductionmentioning
confidence: 99%
“…5 Maryam et al 6 made classification of Heart sound signal using feature extraction techniques of curve fitting and Mel frequency cepstrum coefficients (MFCC) but absence of localization feature it performed misclassification of heart sound signals S 1 and S 2 . Another approach was made for classification of heart sound by He et al, 7 based on AR Modeling it also leads towards misclassification of signal due to less numbers of appropriate features. Further, efforts were made by Barma et al 8 for detection of third heart sound also, using non-linear signal decomposition and time–frequency localization but it fails in term of computational cost.…”
Section: Introductionmentioning
confidence: 99%